Cocoa Bean Shell Flour Concentration Affects Cookie Sensory Acceptance - Binalopa, Thitin; Julyaningsih, Andi Hermina; Syam, Rahman (Jurnal Biologi Tropis, 2026)
Utilization of agro-industrial waste as a raw material for functional food is one way to increase product added value while reducing waste. Cocoa bean husk is a byproduct of cocoa processing that still contains dietary fiber and bioactive compounds, making it potentially useful in pastry products. This study aimed to evaluate the effect of adding cocoa bean husk flour on the organoleptic quality of pastries, including color, aroma, taste, and texture. The study used a design with four concentration treatments of cocoa bean husk flour, namely A0 (0%), A1 (5%), A2 (7.5%), and A3 (10%). Organoleptic tests were conducted using a hedonic scale of 1–5 by 15 semi-trained panelists. Data were analyzed using analysis of variance and further tests at a significance level of 5%. The results showed that the addition of cocoa bean husk flour significantly affected the attributes of color, taste, and texture, but did not significantly affect aroma. Treatment A1 (5%) produced the highest taste scores (4.07 ± 0.70) and texture (4.27 ± 0.70) and still had a good level of color and aroma acceptance. Increasing the flour concentration to 10% tended to decrease panelists' preference, particularly for flavor attributes due to increased bitterness, thought to be due to phenolic compounds. The results showed that cocoa bean hull flour has the potential to be used as an additive in cookies, with the best acceptance at a concentration of 5%.